The Impact of Horizontal Resolution on Projected Sea‐Level Rise Along US East Continental Shelf With the Community Earth System Model. (27th April 2022) - Li, Dapeng; Chang, Ping; Yeager, Stephen G.; Danabasoglu, Gokhan; Castruccio, Frederic S.; Small, Justin; Wang, Hong; Zhang, Qiuying; Gopal, Abishek
Abstract: The Intergovernmental Panel on Climate Change Fifth Assessment Report lists sea‐level rise as one of the major future climate challenges. Based on pre‐industrial and historical‐and‐future climate simulations with the Community Earth System Model, we analyze the projected sea‐level rise in the Northwest Atlantic Ocean with two sets of simulations at different horizontal resolutions. Compared with observations, the low resolution (LR) model simulated Gulf Stream does not separate from the shore but flows northward along the entire coast, causing large biases in regional dynamic sea level (DSL). The high resolution (HR) model improves the Gulf Stream representation and reduces biases in regional DSL. Under the RCP8.5 future climate scenario, LR projects a DSL trend of 1.5–2 mm/yr along the northeast continental shelf (north of 40° N), which is 2–3 times the trend projected by HR. Along the southeast shelf (south of 35° N), HR projects a DSL trend of 0.5–1 mm/yr while the DSL trend in LR is statistically insignificant. The different spatial patterns of DSL changes are attributable to the different Gulf Stream reductions in response to a weakening Atlantic Meridional Overturning Circulation. Due to its poor representation of the Gulf Stream, LR projects larger (smaller) current decreases along the north (south) east continental slope compared to HR. This leads to larger (smaller) trends of DSL rise along the north (south) east shelf in LR than in HR. The results of this study suggest that the better resolved ocean circulations in HR can have significant impacts on regional DSL simulations and projections. Plain Language Summary: Projecting future sea‐level rise has great socioeconomic value. Based on long‐term global high‐resolution Community Earth System Model simulations, we analyze future sea‐level rise in the Northwest Atlantic Ocean. Two identical sets of simulations were conducted with different horizontal resolutions. Comparisons between the two sets of simulations show different sea‐level rise projections along the US east continental shelf between the low‐resolution (LR) and high‐resolution (HR) models. At the northeast shelf, HR projects a sea‐level rise of 0.8 mm/yr, less than half of the trend (1.7 mm/yr) projected by LR. At the southeast shelf, HR projects a sea‐level rise of 0.6 mm/yr, while the trend in LR is statistically insignificant at only 0.15 mm/yr. We attribute the different sea‐level rise projections to the different ocean circulations simulated in LR and HR. Under global warming, LR projects a decrease in Gulf Stream flow along the entire east continental slope, while the decrease in Gulf Stream strength is confined to the southeast continental slope in HR. This study provides an explanation for the discrepancy in regional sea‐level rise projections between low‐ and high‐resolution climate models and thus improves our understanding of projected future sea‐level rise. Key Points: The high resolution (HR) Community Earth System Model reduces biases in dynamic sea level (DSL) and circulation on US east continental shelf Compared to the low resolution model, the HR projects enhanced (reduced) trends of DSL rise along the US south (north) east continental shelf Different DSL rise patterns are related to different Gulf Stream reductions under a weakening Atlantic Meridional Overturning Circulation